2019
DOI: 10.1155/2019/9602935
|View full text |Cite
|
Sign up to set email alerts
|

Melittin Inhibits Hypoxia-Induced Vasculogenic Mimicry Formation and Epithelial-Mesenchymal Transition through Suppression of HIF-1α/Akt Pathway in Liver Cancer

Abstract: In this study, we investigated whether melittin could suppress hypoxia-induced vasculogenic mimicry (VM) formation in liver cancer and explored the underlying mechanisms. Melittin significantly inhibited the proliferation of liver cancer cells with or without CoCl2 presence. Melittin also significantly inhibited CoCl2-induced migration, invasion, and VM formation of liver cancer cells. CoCl2 treatment suppressed the expression of E-cadherin and elevated the expression of N-cadherin and Vimentin. Melittin rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Melittin has been confirmed as an inhibitor in the process of tumor angiogenesis and metastasis. In the study, melittin inhibits liver cancer through suppressing hypoxia-induced VM formation [118]. Both thalidomide and rapamycin target VEGF to inhibit tumor VM formation [119,120].…”
Section: Clinical Significance Of Vm In Cancermentioning
confidence: 99%
“…Melittin has been confirmed as an inhibitor in the process of tumor angiogenesis and metastasis. In the study, melittin inhibits liver cancer through suppressing hypoxia-induced VM formation [118]. Both thalidomide and rapamycin target VEGF to inhibit tumor VM formation [119,120].…”
Section: Clinical Significance Of Vm In Cancermentioning
confidence: 99%
“…The presence of such pathological pseudo blood vessels in tumor tissue indicates poor patient prognosis. Studies have reported that the expression of HIF‐1α was associated with VM channels, as well as with the growth and potential proliferation of tumor cells . When oxygen supply is far less than the demand, tumor cells enter an anoxic state and then form VM channels.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of CD133 + cells in maintaining the characteristics of stem cells as well as the regulatory mechanisms of EMT have been substantially discussed. 14,37 Many genes and related signal pathways are found involved in the gene expression profile of CD133 + subpopulation of various tumors, including the STAT3/PI3K/AKT pathway. 14,38 In addition, the STAT3/ PI3K/AKT pathway was also closely related to EZH2mediated EMT progression.…”
Section: Dovepressmentioning
confidence: 99%